Fluorothymidine PET/CT in Neurolymphomatosis. (May 2015) - Biswal, Chinmoy Kumar; Mittal, Bhagwant Rai; Shukla, Jaya; Vatsa, Rakhee; Bhattacharya, Anish; Prabhakar, Sudesh
<x xml:space="preserve">Abstract</x> Abstract Neurolymphomatosis, a rare extranodal lymphoma, may involve the cranial nerves, peripheral nerves, spinal nerve roots, or nerve plexus. 18F-FDG PET/CT however shows increased FDG uptake in the nerves but is not specific for malignancy. We report a patient with neurolymphomatosis who underwent 18F-FDG PET/CT and 18F-fluorothymidine PET/CT where both the scans showed increased tracer uptake in the right sciatic nerve, proven later as neurolymphomatosis on nerve biopsy. Furthermore, the 18F-FDG avid mediastinal lymph nodes did not show 18F-fluorothymidine avidity, suggesting an inflammatory etiology.